High-loading and high-performance zinc ion batteries enabled by electrochemical conversion of vanadium oxide cathodes. (20th May 2022) - Ren, Jie; Hong, Ping; Ran, Yan; Wang, Bingsen; Chen, Ting; Wang, Yude
Highlights: CaVOH with unique three-dimensional network structure was synthesized on grown on carbon cloth. A new in-situ electrochemical conversion mechanism of vanadium oxide cathode is proposed Transformation product Zn2 (V3 O8 )2 @CC as ZIBs cathodes exhibit high loading, high capacity, and long cycle performances. Abstract: Zinc ion batteries (ZIBs) have become highly competitive in large-scale energy storage applications due to their safety, low cost, and environmental friendliness. However, the cathode materials reported in the literature have the problem of low load (generally less than 3 mg cm ‒2 ), which is difficult to meet the needs of industrial production. In this study, a three-dimensional network structure of calcium ion intercalated vanadium oxide cathode (CaVOH) is grown on carbon cloth (CC) by the one-step hydrothermal method. The cathode has a unique three-dimensional network structure and high mass load (∼ 7 mg cm ‒2 ), high specific capacity (228.5 mAh g ‒1 at 1 A g ‒1 current density), excellent rate performance, and qualified cycle performance (70 % residual after 800 cycles). In Zn(CF3 SO3 )2 electrolyte, CaVOH@CC is transformed into Zn2 (V3 O8 )2 @CC (ZVO@CC) cathode by electrochemical induction. Compared with vanadium oxide cathode synthesized on carbon cloth (VOH@CC), ZVO@CC cathode has lower charge transfer resistance and higher capacitance contribution, which means that it has a better specific capacity, rate performance, and cycle stability. This work provides a new idea for the mechanical explanation of ZIB and a feasible scheme for the design of industrial ZIBs. Graphical abstract: Graphical abstract Image, graphical abstract .